Using Micro-Content Modules to Enhance Students’ Critical Reading Ability - Pinchai, Piansin; Sojisirikul, Phanitphim (rEFLections, 2024)
This study set out to accomplish two main goals: first, an assessment of how well micro-content modules improved students’ critical reading abilities, and second, a look at students’ attitudes and perspectives on incorporating micro-content modules into critical reading instruction. A quasi-experimental methodology was used to achieve these goals, giving treatment group (n = 28) participants access to nine different critical reading micro-content modules and control group (n = 26) participants traditional language teaching. Critical reading assessments were administered to both groups before and after the implementation, with only the treatment group providing feedback on the efficiency of the micro-content modules. The results showed significant improvements in the treatment group’s critical reading skills compared to the control group. The micro-content modules’ convenience, use, visual and auditory clarity, support for self-directed learning, and critical thinking promotion were highly praised by treatment group participants. They also suggested adding more participatory and exciting activities to enhance the long-term success of these modules.